ANALISIS TATA KELOLA KEAMANAN SISTEM INFORMASI RUMAH SAKIT BHAYANGKARA SESPIMA POLRI JAKARTA MENGGUNAKAN COBIT 2019 - Rizqi Satria Andhika Gusni (2021)
Hospitals are health care facilities that need to be supported by a hospital information system (SIM-RS) and secure information security. The problems that occur at the Bhayangkara Sespima Police Hospital in Jakarta are the lack of optimal management of information system security, security that is still lacking and the lack of HR compliance with SOPs. This study uses COBIT 2019 as an assessment framework because COBIT 2019 is a collection of best practices of governance in a company, therefore researchers are interested in examining whether the governance process at the Sespima Bhayangkara Police Hospital in Jakarta has met the criteria of these best practices, especially in governance. security. The domains used in this research are EDM, APO, and DSS with processes EDM03, APO12, APO13, APO14, and DSS05. The results of this study indicate that the level of governance capability at Bhayangkara Sespima Police Hospital Jakarta is at level 3 (Defined), the main problem is in the security service management process (DSS05) and the gap analysis difference from all processes is 1 level below the expected level. Therefore, the results of this study are expected to be followed up by the Bhayangkara Sespima Police Hospital in Jakarta on the governance of information system security.